The Influence of Ligand Density and Degradability on Hydrogel Induced Breast Cancer Dormancy and Reactivation. Issue 11 (30th April 2021) - Farino Reyes, Cindy J.; Pradhan, Shantanu; Slater, John H.
Abstract: The role of hydrogel properties in regulating the phenotype of triple negative metastatic breast cancer is investigated using four cell lines: the MDA‐MB‐231 parental line and three organotropic sublines BoM‐1833 (bone‐tropic), LM2‐4175 (lung‐tropic), and BrM2a‐831 (brain‐tropic). Each line is encapsulated and cultured for 15 days in three poly(ethylene glycol) (PEG)‐based hydrogel formulations composed of proteolytically degradable PEG, integrin‐ligating RGDS, and the non‐degradable crosslinker N‐vinyl pyrrolidone. Dormancy‐associated metrics including viable cell density, proliferation, metabolism, apoptosis, chemoresistance, phosphorylated‐ERK and ‐p38, and morphological characteristics are quantified. A multimetric classification approach is implemented to categorize each hydrogel‐induced phenotype as: 1) growth, 2) balanced tumor dormancy, 3) balanced cellular dormancy, or 4) restricted survival, cellular dormancy. Hydrogels with high adhesivity and degradability promote growth. Hydrogels with no adhesivity, but high degradability, induce restricted survival, cellular dormancy in the parental line and balanced cellular dormancy in the organotropic lines. Hydrogels with reduced adhesivity and degradability induce balanced cellular dormancy in the parental and lung‐tropic lines and balanced tumor mass dormancy in bone‐ and brain‐tropic lines. The ability to induce escape from dormancy via dynamic incorporation of RGDS is also presented. These results demonstrate that ECM properties and organ‐tropism synergistically regulate cancer cell phenotype and dormancy. Abstract : Forming a better understanding of how extracellular matrix properties influence cancer cell fate is key in understanding the mechanisms that initiate and maintain cancer dormancy. Three unique hydrogel formulations with varied ligand (RGDS) density and degradability are implemented to induce growth, four distinct dormancy states, and reactivation in parental MDA‐MB‐231s and three organotropic 231 sublines.